Actualization of the meaning cleanliness is half of faith in improving environmental health through the waste bank program - Diah Wahyuningsih; Happy Agustiani; Ezif Rizqi Imtihana (Journal of Interdisciplinary Islamic Studies, 2022)
Rapid growth is considered to be the main reason for the amount of waste. The Waste Bank Program is one of the ways to manage waste and minimize its presence in the environment. The purpose of this study was to analyze the actualization of the meaning of the hadith about cleanliness as part of the faith through the waste bank. This research method uses a descriptive method through a survey. Based on this research, the Waste Bank is one of the solutions to help deal with waste management in Indonesia. The concept of a waste bank is a form of actualizing the meaning of cleanliness as part of faith. Waste Banks are one of the efficient alternative solutions in improving environmental health as an actualization of the meaning of Islamic teachings.